PROSEDUR PELAYANAN BANQUET WAITER DALAM MENANGANI TAMU EVENT DI HOTEL ASTON PASTEUR BANDUNG - Fauzzia, Willma; Pradana, Randy (LPPM Politeknik Pajajaran ICB Bandung, 2023)
Hotel is one of the accommodation facilities that provides various facilities to meet the needs of hotel guests, as well as tourists, ranging from places to stay to food and beverage needs which are managed with the aim of making a profit. Hotels of course need parts or departments that can support their operational activities. Food and Beverage Service is one part of the Food and Beverage Department at the hotel which is responsible for serving and fulfilling food and beverage needs, both in providing and serving it to guests. In this study, researchers used qualitative methods through a descriptive approach by collecting data through observation, interview and documentation techniques. Based on the research results obtained and the discussion that has been described, it can be concluded that Banquet Waiter has a vital role in the continuity of operations at the Aston Pasteur Hotel by handling the organization of an event to be held, starting from the preparation, during operation, to closing stages. The purpose of this research is to find out how the Standard Operating Procedures are in serving event guests as a Banquet Waiter at Aston Pasteur Hotel.